Lend wings to Calvinism! CHE international action - Walt, Barend Johannes van der (Koers, 1978)
There is growing realisation at the PU for CHE that it not only has a duty internally (towards its students and lecturers) or nationally, but that it also has a mission on the international level. This growing consciousness of a worldwide dedication to service has gained substance especially since the First International Conference of Institutions for Christian Higher Education (September, 1975, at Potchefstroom).